Temporal wavelet analysis for deformation measurement of small components using micro-ESPI - Fu, Yu (2010)
Measuring continuous deformation of specimens whose dimensions are in the range of sub-millimeter introduces a number of difficulties using laser speckle interferometry. During deformation, the speckle patterns recorded on a camera sensor change constantly. These time-dependent speckle patterns would provide the deformation history of the object. However, compared to large objects, noise effect is much more serious due to the high magnification. In this study, a series of speckle patterns on small objects are captured during deformation by high speed camera and the temporal intensity variation of each pixel is analyzed by a robust mathematical tool --- complex Morlet wavelet transform instead of conventional Fourier transform. The transient velocity and displacement of each point can be retrieved without the need for temporal or spatial phase unwrapping process. Displacements obtained are compared with those from temporal Fourier transform, and the results show that wavelet transform minimize the influence of noise and provide better results.